Offshoring, employment and wages - Alessandro Bramucci (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2016)
This paper reviews the debate on the economic effect of the international fragmentation of production, also known as "offshoring", and provides a preliminary investigation of the impact of intermediate imported inputs on employment and wages in five European countries (Germany, Spain, France, Italy, the United Kingdom). Data are obtained from the Sectoral Innovation Database (SID) of the University of Urbino, a large database that merges statistical material from various sources (LFS; CIS; WIOD). The first part of this work provides a review of the empirical literature that discusses the economic effects of offshoring on domestic labor demand and wages. The second section of the paper presents offshoring trends and discusses the results of the econometric analysis. Results suggest that offshoring has a general negative impact on employment and wages although more careful examination reveals that high-tech offshoring has a positive effect on wages of medium- and high-skilled workers.
Keywords: F1; F2; 330; Offshoring; Innovation; Employment; Wages